A clínica da imagem: projeções do fundo-mundo para in-surgir a vida - Lobo, Taís Ribeiro (2022)
The relationship between cinema and the colonial unconscious proposes subversions in Latin American modes of subjectivation, through the search for the decolonization of images produced for screens and for lives, and the ways of making cinema and clinic. This aestheticvital co-creation gives rise to abyssal plots that can collapse the order of sociopolitical reality, sowing a healthy process of insurgency to this colonial-capitalist regime. This research proposes to create an essay on cinema and its respective cinematographic making as a technology of diving into the codes of the colonial unconscious, in order to defragment it to promote the germination of life in the context of the radicalized struggles carried out by some aspects. of Latin American anti-colonial activism. From a series of audiovisual laboratories applied over the last ten years, in instances and spaces of micropolitical resistance that I will call “Clinic of the Image”, it is intended, first, to take an xray of the depths present there to understand which images are projected on the surface, generating encounters, care and plots that guarantee the continuity and consistency of these actions on screens and in struggles. To this end, the films Anchoring Ships in Space #03 - Decolonizing Passions, The Verb and the images generated in the Camera-Body and Witchcraft laboratory will be portrayed, co-directed by me in partnership with other artists and activists. Latin American films with clues to a cinema that manages life in its community and collective aspects will also be screened. Likewise, it will seek to reflect on how these images - in movement, can create a cosmology of feminist actions in therapeutic and audiovisual care technologies for the creation of insurgent and abundant worlds